The Effect of Sharia Financial Literacy, Sharia Financial Inclusion, and Motivation on Interest in Saving in Sharia Banks with Religiosity Moderation - Ardelia Putri; Santi Yustini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The importance of understanding the factors that influence people's interest in saving in Islamic banks. This study aims to analyze the influence of Islamic financial literacy, Islamic financial inclusion, and motivation on the interest in saving in Islamic banks with moderation of religiosity (a case study in the South Tangerang community). The population in this study was the South Tangerang community with a sample of 100 respondents. The sampling used non-probability with a purposive sampling technique with a Likert scale . The data analysis method used SEM-PLS with SmartPLS 4.0 software. The results of this study indicate a significant influence between the Islamic financial inclusion variable on the variable of interest in saving, a significant influence between the motivation variable on the variable of interest in saving, while the Islamic financial literacy variable has no significant influence on the variable of interest in saving. On the other hand, the religiosity variable is unable to moderate the relationship between the variables of Islamic financial literacy, Islamic financial inclusion, and motivation on the interest in saving.